Updates on Clostridium difficile in Europe Advances in Microbiology, Infectious Diseases and Public Health Volume 8 (Advances in Microbiology, Infectious Diseases and Public Health, 2018)
This book outlines the currently available clinical, epidemiological and experimental data on Clostridium difficile infection (CDI) with special emphasis on studies and results achieved in Europe. The incidence and severity of CDI has increased significantly over the last decade, and the book explains why C. difficile, recently reclassified as Clostridioides difficile, remains a significant challenge, also from economic perspective, to health care systems all over the world. The different reservoirs of this ubiquitous microorganism are reviewed as well as the different factors contributing to its virulence, such as toxins and biofilm formation. The rapid evolution of antibiotic resistance is clearly a concern and in a specific way can influence the CDI epidemiology. Additionally, new emerging strains and comparative genomics studies are discussed for their relevance from epidemiological and evolutionary point of view. The book also gives an overview on diagnostics, therapy and surveillance, all of which are still challenging. Therefore, a closer look is taken on the effect of probiotics as an alternative to antibiotics, for prevention and treatment of CDI. Fecal transplantation from healthy donors, passive immunotherapies and vaccines for patients with recurrences are also discussed in dedicated chapters. The book closes with a summary of the history and the achievements of the European Society of Clinical Microbiology and Infectious Diseases Study Group for Clostridium difficile (ESGCD) written by the current and past presidents of the Society. It is the aim of this book to raise awareness on CDI and to disseminate updated information on its prevention, diagnosis and treatment.